Role of Macrophage in Type 2 Diabetes Mellitus: Macrophage Polarization a New Paradigm for Treatment of Type 2 Diabetes Mellitus - Banu, Sarmin; Sur, Debjeet (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Metabolic diseases such as type 2 diabetes mellitus are usually associated with meta-inflammation. β-cell failure is a marked feature observed in the pathogenesis of type 2 diabetes mellitus. Type 2 diabetes mellitus (T2DM) is a heterogeneous situation that is accompanied by not only defective insulin secretion but also peripheral insulin resistance. β-cells are the primary organ for insulin secretion; hence, it is crucial to maintain a significant β-cell mass in response to a variety of changes. Insulin resistance is a chief cause of T2DM, leading to increased free fatty acid (FFA) levels, which in turn elevates β-cell mass and insulin secretion as compensation for insulin insensitivity. It has recently been established that amplified numbers of innate immune cells, cytokines, and chemokines result in detrimental effects on islets in chronic conditions. Macrophage migration inhibitory factor (MIF) is the lymphokine that prevents arbitrary migration of macrophages and assembles macrophages at inflammatory loci. Inflammation is known to trigger monocytes to differentiate into macrophages. Progress of complications associated with type 2 diabetes mellitus, as indicated through recent findings, is also dependent on the buildup of macrophages in tissues vulnerable to diabetic injury. The present article scientifically evaluates the present knowledge concerning the mechanisms of monocyte and macrophage-mediated injury recruitment in complications associated with type 2 diabetes mellitus. It also describes some of the established and experimental therapies that might bring about a reduction in these inflammatory complications. Recent discoveries in the field of drug delivery have facilitated phenotype-specific targeting of macrophages. This review highlights the pathophysiology of type 2 diabetes mellitus, how macrophage induces type 2 diabetes mellitus and potential therapeutics for type 2 diabetes mellitus via macrophage-specific delivery.
Keywords: macrophages